Best practices in capturing employee creativity: forest sector firms in the USA and Finland. (2nd January 2017) - Laukkanen, V.; Siimekselä, M.; Leavengood, S.; Hansen, E.
Abstract : Practices for capturing employee creativity present an important opportunity for forest sector firms wishing to increase their innovation efforts. Since employees are the interface with customers and business processes, they are best positioned to have the insights necessary for improvements. Despite this obvious connection, the forest sector literature has only rarely addressed the mechanisms that might be used by forest industry companies to capture and implement employee creativity and ideas for innovation. Accordingly, this exploratory study investigates best practices utilised in four innovative firms. Using a qualitative approach, we find many commonalities among these firms. For example, each company provides autonomy to work teams and is open to employee ideas for improvement. Two of the four companies rely on customers for ideas. Based on these findings, we conclude that competitive advantage in the forest sector of the twenty-first century is also tied to people, in addition to raw materials or equipment.